Real-time ultrasound-guided lumbosacral epidural anaesthesia in obese or appropriate body condition score dogs: A randomized clinical trial - Credie, L. F.G.A. [UNESP] (2022)
Correctly identifying the puncture site and needle position in obese dogs can be challenging to achieve epidural anaesthesia. The current study aimed to evaluate a real-time ultrasound-guided technique, to perform epidural anaesthesia in obese or appropriate body condition score dogs, based on visualization of local anaesthetic flow during its injection, compared to the traditional method of palpation of anatomical landmarks. Seventy-two client-owned dogs were evaluated in a prospective, comparative, randomized clinical trial, allocated into four groups of 18 dogs. For the Palpation-guided 1 (PG1) and 2 (PG2) groups, epidural anaesthesia was based on palpating anatomical landmarks. Dogs with a body condition score (BCS) 1-5/9 were included in the PG1 (non-obese), and those with a BCS 6-9/9 in PG2 (obese) groups. In the Ultrasound-guided 1 (USG1 - BCS 1-5/9) and 2 (USG2 – BCS 6-9/9) groups, epidural anaesthesia was guided by ultrasound (US). The flow of anaesthetic through the epidural canal was observed in all dogs by US. There were fewer needle-to-bone contacts in the US-guided groups when performing epidural anaesthesia; this only occurred on the vertebral laminae, never in the vertebral canal. Ultrasound guidance enabled local anaesthetic injection into the epidural space without the need for palpation of anatomical landmarks to guide needle placement. Blood reflux occurred in 11.1% (PG1), 22.2% (PG2), 5.5% (USG1), and 0% (USG2) of the dogs. Ultrasound-guided punctures led to fewer vascular punctures. Epidural anaesthesia was effective in all animals, and no complications were observed.